2014 atomic spectrometry update – a review of advances in environmental analysis. Issue 1 (20th November 2014) - Butler, Owen T.; Cairns, Warren R. L.; Cook, Jennifer M.; Davidson, Christine M.
Abstract : This review covers advances in environmental analysis published between August 2013 and July 2014. Abstract : This is the 30th annual review of the application of atomic spectrometry to the chemical analysis of environmental samples. This Update refers to papers published approximately between August 2013 and July 2014 and continues the series of Atomic Spectrometry Updates (ASUs) in environmental analysis 1 that should be read in conjunction with other related ASUs in the series, namely: clinical and biological materials, foods and beverages, 2 advances in atomic spectrometry and related techniques, 3 elemental speciation, 4 X-ray fluorescence spectrometry, 5 and the analysis of metals, chemicals and functional materials. 6 In the field of air analysis, highlights within this review period included: the use of 3D printing technology for the rapid prototyping of new air sampler components; single particle ICP-MS studies; use of a new triple-quadrupole ICP-MS for the analysis of radioactive species and the use of FEG-SEM and IBA for the analysis of gun-shot residues. In the field of water analysis, methods continue to be developed: for the extraction and preconcentration of elements; speciation of As, Cr, Hg and Sb forms and determination of elemental constituents in colloidal and NP fractions. Instrumental developments reported include the use of MC-ICP-MS for isotopic tracer studies and a review of XRF techniques and associated preconcentration procedures for trace element analysis. Many articles featuring the analysis of plants and soils appeared but, as usual, most focused on environmental applications rather than the advancement of atomic spectrometry. There have, however, been interesting developments, such as the almost bewildering increase in types of micro-extraction for analyte preconcentration and the resurgence of CS-AAS. Clearly LIBS is maturing rapidly, with soil analysis becoming more routine in nature. Also notable was the way the accident at the Fukishima-Daiichi nuclear power plant triggered development of analytical methods for the assessment of contamination in the surrounding area. Recent research indicates that geological applications still drives many of the instrumental and methodological advances in LA-ICP-MS. Fundamental studies continue to shed light on the processes involved and hence ways of improving the analysis of laser-produced aerosols. The preparation of NP powders for the production of matrix-matched RMs for microanalytical techniques such as LA-ICP-MS and SIMS showed great promise for addressing one of the major issues when analysing geological materials by these techniques. Steady advances in MC-ICP-MS methodology is feeding through to applications in isotope geochemistry, while new SIMS instrumentation is being directed towards probing fine growth structures in biogenic carbonates and inferring past climate conditions from their geochemistry. Feedback on this review is most welcome and the review coordinator can be contacted using the email address provided.